Does emotional restraint or exuberance get you the job? How and when enthusiasm intensity is related to perceived job suitability. Issue 2 (18th July 2022) - Stollberger, Jakob; Shemla, Meir; de Cremer, David; Yang, Yu; Sanders, Karin
Abstract: Scholars have identified that interviewers prefer applicants who are both emotionally restrained and exuberant. To reconcile these inconsistent results, we investigated how the magnitude of applicants' expressed enthusiasm influences interviewer perceptions of job suitability. In two experimental studies with recruiters in China, we show that expressing intense as opposed to mild enthusiasm reduces applicants' chances to be perceived as suitable for the job (Study 1). We further demonstrate that expressions of intense enthusiasm do not always undermine their perceived job suitability but can also lead to a positive interview outcome. We find that the negative consequences of intense enthusiasm are explained by interviewer perceptions of decreased appropriateness, whereas the positive consequences are driven by interviewer perceptions of the applicant's attraction to the organization (PAAO; Study 2). We also report how interviewer trait information processing motivation (IPM) influences the way applicants expressing intense enthusiasm are evaluated. Only interviewers with low trait IPM interpret applicants' intense enthusiasm as less appropriate. We propose to incorporate the social signaling character of emotions in future theorizing and research on nonverbal communication in job interviews.